Clinical evaluation of Bio-Rad MRSASelect™ medium for the detection of livestock-associated methicillin-resistant Staphylococcus aureus - Verkade, E. (Springer-Verlag, 2010)
Bio-Rad MRSASelect™ medium was evaluated for its ability to recover methicillin-resistant Staphylococcus aureus (MRSA) from nasal samples of pig farmers and their household members. In total, 257 samples were inoculated on Bio-Rad MRSASelect™ medium with and without broth enrichment and on bioMérieux MRSA ID with broth enrichment. A sample was considered to be positive if at least one of the media grew MRSA. The sensitivity of Bio-Rad MRSASelect™ medium without broth enrichment was 63.9%. With broth enrichment, the sensitivity increased to 98.4%. The specificity was 95.4% both with and without broth enrichment. In conclusion, Bio-Rad MRSASelect™ medium as well as MRSA ID medium are reliable methods to detect MRSA carriage when used in combination with broth enrichment. The directly inoculated MRSASelect™ medium was statistically significantly less sensitive than the two media after broth enrichment.